On the Degree of Approximation of Continuous Functions by Means of Fourier Series in the Hölder Metric (Analysis in Theory and Applications, 2020)
In this paper we prove two theorems on the degree of approximation of continuous functions by matrix means related to partial sums of a Fourier series in the Hölder metric. These theorems can be taken as counterparts of those previously obtained by T. Singh [3].
Keywords: Matrix transformation; degree of approximation; Fourier series; Hölder metric.